Interlayer coupling in Tb/Fe bilayers and Tb/Au/Fe trilayers with sharp or rough interface - Shypil, E. V.; Pogorily, A. M.; Podyalovski, D. I.; Pogoryelov, Y. A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
Bilayer films Fe/Tb (Tb on Fe) having sharp and Tb/Fe (Fe on Tb) having rough interface were prepared by molecular beam epitaxy to study interlayer magnetic coupling. Magnetic properties of these bilayers were characterized ex situ using ferromagnetic resonance (FMR), polar magneto-optical Kerr effect and SQUID magnetometer. The resulting perpendicular magnetic anisotropy (PMA) is discussed as an effect of interlayer magnetic coupling. PMA was observed in rough as well as in sharp interfaces and the anisotropy energies were estimated. When a monolayer of Au was interposed at the interface of both kinds, PMA was observed to disappear and the overall magnetic moment increased. It was also shown that in ultrathin films demagnetization factor depends on the substrate roughness and should be considered in the FMR data.